Zakah on income of Islamic banks as income tax deduction in Nigeria : lessons from Malaysia - Zubaedy, Abdul Ganiyi Abdurroheem (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2016)
Nigeria operates a dual banking system where both Islamic and conventional banks co-exist and both are liable to income tax on their total profits, less a permitted deduction by law. Under the Nigerian Banking Regulations, the “Profit After Tax” (PAT) otherwise known as “Net Profit” of a bank is further liable to deduction of certain percentages known as “retained earnings” and “reserves”. These funds are specifically meant for the purposes of banking re-investment and liabilities. However, from the Islamic law perspectives, the re-invested retained earnings on the profit generating assets and their proceeds are income of the bank considered as belonging to the shareholders collectively, being part of their distributable profits held and retained from the net profit. Therefore, this income is jointly subject to zakāh in the hand of Islamic banks based on the principle of al-Khulṭah (joint wealth) and such zakāh is deemed paid on behalf of the shareholders in that circumstance. This is so notwithstanding the zakah due on the dividends and shares by the shareholders themselves as their personal income. Islamic banks thus, bear additional financial obligation of “zakah” on the income legally meant for development after the “income tax”. These double financial obligations somehow put the Islamic banking industry in Nigeria at some disadvantages compared with its conventional counterparts, as the zakah obligation on retained earnings may discourage the investors, who normally gauge and measure the performances and prosperities of a company by the size and increase in its retained earnings, from investing with Islamic banks. This study, therefore, examines this problem in a bid to providing a means for addressing it. The research adopts doctrinal legal research methodology and, as such, basically relies on the available literature on the subjects of Islamic banking, taxation and zakah, which are in both printed and electronic forms. A thorough content analysis of the materials were done and at the end of the study, it was found that the major factor responsible for this problem in Nigeria is the current state of the Companies Income Tax law that has not yet given recognition to compensation and incentive for the zakāh payment made by Islamic banks. This seems to discourage the existing Islamic banking outlets in the country from paying the zakāh due on their retained earnings. For instance, Jaiz Bank Plc, the only full-fledged Islamic bank in the country, did not reflect payment of zakah in its relevant Annual Financial Reports of 2014 as closely studied in this work. Accordingly, this research proposes a specific amendment to the current Companies Income Tax Act 2007 (as amended) to allow the zakāh paid by Islamic banks on their income during the tax assessment year to be treated as income tax deduction. This is by borrowing a leaf from Malaysia that has already amended its taxation law to accommodate deduction of zakāh from income tax liabilities.